Rebranding of Poso Regency Tourism After Social Conflict - Andi Akifah; Rizqy Alfiyaty; Nabillah Sasha Monica (Jurnal Penelitian Komunikasi dan Opini Publik, 2021)
After the social conflict with the issue of ethnicity, religion, race and inter-group. the image of Poso Regency has changed to become a "City of Conflict". This study aims to determine the rebranding process carried out by the Poso Regency Tourism Office in changing the image as a conflict area that is already attached. This study uses qualitative methods through observation and in-depth inteviews with selected informants by purposive sampling technique. The results of the study shows that in carrying out the rebranding process, the Poso regency tourism office has done several things, including trying to promote its area as a safe, peaceful and fair area through participation in various tourism events at both domestic and overseas; Cooperating with security forces in creating safe conditions in the Poso Regency area; Changing the tourism tagline, which was originally “mandago-dago ri tanah Poso”, then became “the land of thousand megaliths” to introduce the uniqueness of Poso land which has many historical relics in the form of megalithic statues. The final process is to publish all changes and carry out large-scale promotions through mass media, both conventional and contemporary